Analisis Kemampuan Kerja dan Kompensasi Terhadap Kinerja Driver Grab di Surabaya - Dwi setiawan, Rizky; Irbayuni, Sulastri (Jurnal Economic Resource, 2025)
This study is titled Analysis of Employability and Compensation for Grab Driver Performance in Surabaya and aims to analyze how these two variables affect performance. The background of this study is based on the phenomenon of declining grab driver performance which is shown through the decrease in the number of downloads of the grab driver application and the existence of complaints from users about the service. The approach used was quantitative with respondents as many as 90 Grab drivers in Surabaya who were selected through purposive sampling techniques. Data analysis was carried out using the Partial Least Square (PLS) method. The results show that both employability and compensation contribute to driver performance. These findings indicate that the higher the level of employability and compensation received, the better the performance of Grab drivers.